TINDAKAN FISIK SUAMI TERHADAP ISTRI PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF: ( Studi Pasal 6 Undang-Undang No. 23 Tahun 2004 Tentang Penghapusan Kekerasan) - Syarif Hidayatulloh, Rheza; Masrokhin; Afif, Abdullah (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2025)
This type of research is library research, the data sources are primary, secondary and tertiary data sources. The data collection techniques used are in the form of laws and regulations, books, journals, papers, articles and others. Using analytical descriptive method. From the results of the study it is concluded that domestic violence in the form of beatings against wives or other forms of physical violence is not justified in positive law, namely in Law No. 23 of 2004 concerning the Elimination of Domestic Violence in any form. In Islamic Law domestic violence is not justified. it is allowed to beat the wife on the grounds of disobedience to the husband, namely with stages by stages. Keywords: Physical Actions, Islamic Law, Positive Law, Violence.